Detectors assessment for stereotactic radiosurgery with cones. (14th September 2018) - Garnier, Nicolas; Amblard, Régis; Villeneuve, Rémy; Haykal, Rodolphe; Ortholan, Cécile; Colin, Philippe; Gérard, Anaïs; Belhomme, Sarah; Mady, Franck; Benabdesselam, Mourad; Serrano, Benjamin
Abstract: The purpose of this work is to assess eight detectors performance for output factor (OF), percent depth dose (PDD), and beam profiles in a 6‐MV Clinac stereotactic radiosurgery mode for cone irradiation using Monte Carlo simulation as reference. Cones with diameters comprised between 30 and 4 mm have been studied. The evaluated detectors were ionization chambers: pinpoint and pinpoint 3D, diodes: SRS, P and E, Edge, MicroDiamond and EBT3 radiochromic films. The results showed that pinpoints underestimate OF up to −2.3% for cone diameters ≥10 mm and down to −12% for smaller cones. Both nonshielded (SRS and E) and shielded diodes (P and Edge) overestimate the OF respectively up to 3.3% and 5.2% for cone diameters ≥10 mm and in both cases more than 7% for smaller cones. MicroDiamond slightly overestimates the OF, 3.7% for all the cones and EBT3 film is the closest to Monte Carlo with maximum difference of ±1% whatever the cone size is. For the profiles and the PDD, particularly for the small cones, the size of the detector predominates. All diodes and EBT3 agree with the simulation within ±0.2 mm for beam profiles determination. For PDD curve all the active detectors response agree with simulation up to 1% for all the cones. EBT3 is the more accurate detector for beam profiles and OF determinations of stereotactic cones but it is restrictive to use. Due to respectively inappropriate size of the sensitive volume and composition, pinpoints and diodes do not seem appropriate without OF corrective factors below 10 mm diameter cone. MicroDiamond appears to be the best detector for OF determination regardless all cones. For off‐axis measurements, the size of the detector predominates and for PDD all detectors give promising results.